Acoustic Switch via a Compressible Minimal Surface Structure. Issue 4 (18th October 2022) - Xue, Pan; Dai, Hongqing; Zhou, Laishui
Abstract : Acoustic metamaterials exhibit novel physical phenomena due to their excellent properties for manipulating the propagation of sound waves. Specifically, acoustic switches are gaining increasing attention due to their enormous potential applications in acoustic sensing and acoustic logical computing. However, acoustic switch elements with simple and stable mechanical properties remain elusive. Herein, an acoustic switch based on the compressible minimal surface structure is proprosed. The acoustic switch is fabricated with a rubber‐like material, exhibiting good compression mechanical properties. The simulation and experiment results show that when the soft structure is compressed, the acoustic signal can be efficiently switched from the OFF state to the ON state. The study provides a guide to design acoustic switches, which exhibit enormous application potential in acoustic signal sensing and fault diagnosis. Abstract : Herein, an acoustic switch based on the compressible p ‐type triply periodic minimal surface (TPMS) structure is proposed. The p ‐type TPMS structure is fabricated with rubber‐like material using 3D printing. The ON/OFF state of an acoustic signal can be easily changed by a slight load change, providing a new route for signal monitoring.